A simplified model for an n-layer elastic foundation = Uproszczony model n-warstwowego podłoża sprężystego - Cyrok, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a model for an elastic foundation consisting of a finite number of homogeneous and isotropic layers. The simplified continuous elastic media with internal constraints introduced by R. Świtka [1] has been adopted for discussion, in which it is assumed that the horizontal components of a displacement vector equal zero. The purpose of the paper is a solution determining the displacement of the foundation surface, caused by a uniform load within a circular area. By means of the Hankel integral transformation and the notion of the layer transfer matrix in the transform domain, a solution to vertical displacements of the foundation surface has been obtained. The method for computing the infinite integral specifying numerical values of displacements of the foundation surface has been presented. The solution concerning the interaction of a uniform load within a circular area presented in the paper can be used for an approximate solution (by computer methods) to the task of the contact between a beam or a raft and the surface of an elastic layer foundation.
Keywords: model podłoża sprężystego; podłoże sprężyste; powierzchnia warstwowa; warstwa jednorodna; obciążenia; elastic layered half space; internal constraints; boundary value problem; computer methods; soil-structure interaction